CdSe nanorod/TiO2 nanoparticle heterojunctions with enhanced solar- and visible-light photocatalytic activity - Laatar, Fakher; Moussa, Hatem; Alem, Halima; Balan, Lavinia; Girot, Emilien; Medjahdi, Ghouti; Ezzaouia, Hatem; Schneider, Raphaël (Beilstein Journal of Nanotechnology, 2017)
CdSe nanorods (NRs) with an average length of ≈120 nm were prepared by a solvothermal process and associated to TiO2 nanoparticles (Aeroxide® P25) by annealing at 300 °C for 1 h. The content of CdSe NRs in CdSe/TiO2 composites was varied from 0.5 to 5 wt %. The CdSe/TiO2 heterostructured materials were characterized by XRD, TEM, SEM, XPS, UV–visible spectroscopy and Raman spectroscopy. TEM images and XRD patterns show that CdSe NRs with wurtzite structure are associated to TiO2 particles. The UV–visible spectra demonstrate that the narrow bandgap of CdSe NRs serves to increase the photoresponse of CdSe/TiO2 composites until ≈725 nm. The CdSe (2 wt %)/TiO2 composite exhibits the highest photocatalytic activity for the degradation of rhodamine B in aqueous solution under simulated sunlight or visible light irradiation. The enhancement in photocatalytic activity likely originates from CdSe sensitization of TiO2 and the heterojunction between these materials which facilitates electron transfer from CdSe to TiO2. Due to its high stability (up to ten reuses without any significant loss in activity), the CdSe/TiO2 heterostructured catalysts show high potential for real water decontamination.
Keywords: CdSe nanorods; heterojunction; photocatalysis; TiO2